Augmented All‐Optical Active Terahertz Device Using Graphene‐Based Metasurface. Issue 16 (24th May 2021) - Choi, Geunchang; Chau, Tuan Khanh; Hong, Sung Ju; Kim, Dasom; Kim, Sung Hyuk; Kim, Dai‐Sik; Suh, Dongseok; Bahk, Young‐Mi; Jeong, Mun Seok
Abstract: Photo‐excited graphene has a positive (semiconductor‐like) or negative (metal‐like) response depending on the Fermi level, which is tuned by gate control, doping, and growth. Both negative and positive photoconductive responses have a potential application as an ultrafast optical modulator in the control of light transmission. However, it is challenging to achieve a high on/off ratio in the photo‐excited graphene because of a small absorption of electromagnetic waves and a limitation of photo‐induced conductivity change. Here, the negative‐type high on/off ratio and ultrafast terahertz modulation are experimentally demonstrated using graphene/metal nanoslot antennas. When the graphene covers the nanoslot antennas, the terahertz waves are completely blocked (off‐state). This perfect extinction results from the enhanced intraband absorption in graphene by strong localized fields near the nanogap. However, once the optical pump is applied to the graphene/nanoslot antennas, terahertz transmission becomes recovered resonantly (on‐state) due to the photo‐induced transparency of graphene that leads to a distinctive modulation from off‐ to on‐resonance. Furthermore, the fast carrier relaxation induced by strong terahertz field‐driven carrier redistribution is responsible for the faster modulation of transient terahertz transmission. The results will open up pathways toward negative‐response terahertz modulation applications with high on/off ratio and ultrafast time scale. Abstract : The high on/off ratio and ultrafast terahertz modulation are demonstrated using metal‐like graphene/metallic nanoslot antennas. The localization of terahertz fields induces 1) the strong terahertz absorption and photo‐induced transparency of the graphene layer that enable to achieve a distinctive modulation from off‐ to on‐resonance, and 2) the faster carrier relaxations originated from strong terahertz field‐driven carrier redistribution.